دورة تكوينية في المرافقة النفسية والتعليمية لتلاميذ السنة خامسة إبتدائي لفائدة المعلمين - بن نوح، إبتسام (جامعة الوادي university of Eloued, 2017)
ملخص الدراسة: هدفت‌الدراسة إلى إعداد دورة تكوينية في المرافقة النفسية والتعليمية لتلاميذ السنة الخامسة من التعليم‌الابتدائي‌لفائدة‌المعلمين‌بالاعتماد على المنهج الشبه التجريبي ذو التصميم القياس القبلي والبعدي للمجموعة الواحدة على عينة مقدرة بـــ :51معلم ومعلمة في الطور الخامس من التعليم الابتدائي تم اختيارهم بطريقة العشوائية للموسم الدراسي 6152/6152وباستخدام أدوات جمع البيانات التي تمثلت في مقياس المرافقة النفسية والمقابلة البحثية وتمثل الأسلوب الإحصائي في اختبار(-ت- بايرد) للدرجات واختبار(ت) للفروق‌وتم التوصل إلى النتائج التالية : - الفرضية الأولى: توجد فروق ذات دلالة إحصائية بين القياس القبلي والقياس البعدي في نتائج المشاركين بعد تطبيق الدورة لصالح القياس البعدي لمتغير المرافقة النفسية . - الفرضية الثانية: لا توجد فروق ذات دلالة‌إحصائية‌في‌أسلوب‌المرافقة‌النفسية والتعليمية لتلاميذ السنة الخامسة الذي يقوم به معلم الطور الخامس ابتدائي تعزى لمتغير الجنس. وبناء عليه تم التحقق من أثر الدورة المعدة التي تهدف إلى تطوير أسلوب المرافقة لتلاميذ السنة الخامسة من التعليم الابتدائي لفائدة المعلمين. وبالتالي تم التأكد من ضرورة توفير مرشدين ومعلمين أكفاء في المدارس لمساعدة التلاميذ على حل مشكلاتهم الد ارسية من خلال الاهتمام ببناء ب ارمج تُعنى بتنمية جوانب م ارفقة تلاميذ الامتحانات النهائية لتحقيق أفصل سبل النجاح فالضرورية.‌ب Study Summary: The study aimed to prepare a training course in the psychological and educational accompaniment of fifth year pupils in primary education for teachers, based on the semi-experimental, pre-experimental, pre-test and pre-test method for one group on a sample estimated at 15 teachers and teachers in the fifth stage of primary education randomly selected for the 2016 academic year (2017). Using the data collection tools represented in the Psychological Accompaniment Scale and the Research Interview, the statistical method is represented in the T-Bird test of the grades and the T-test of the differences. The following results were obtained: - The first hypothesis: There are statistically significant differences between the tribal measurement and post-measurement in the results of the participants after the application of the course in favor of the post-measurement of the variable psychological accompaniment. - The second hypothesis: There are no significant differences in the method of psychological and educational accompaniment of the fifth year students carried out by the fifth phase primary teacher attributed to the gender variable. Accordingly, the impact of the preparatory course aimed at developing the method of accompanying fifth-grade pupils to primary education for teachers was verified. It is therefore necessary to provide qualified teachers and teachers in schools to help students solve their school problems by focusing on building programs to develop the aspects of accompanying the final exam students to achieve the most necessary means of success.
دراسة ميدانية شبه تجريبية بمقاطعة جامعة رقم 12 لولاية الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: المرافقة النفسية، تكوين المعلمين; Accompagnement psychologique, formation des enseignants; Psychological accompaniment, Teacher training